Are Vitamin and Herbal Supplements an Effective Complementary and/or Alternative Method of Treating and Maintaining Remission in Inflammatory Bowel Disease?: A Systematic Review - Sadler, Grace Sylvia Peers (2013)
Objective: To conduct a systematic review and critically appraise research on the effectiveness of vitamin and herbal supplements as complementary and/or alternative medicine as part of the treatment and management for symptoms related to inflammatory bowel diseases (IBD). Method: Search for relevant journals on 2 electronic databases, CINHAL and PubMed with the use of predefined inclusion criteria. The validity of the studies was evaluated using the CONSORT checklist, as a quality assessment tool. Two reviewers independently appraised each included study. Results: Overall, seven studies were included in this review. The quality of all of the studies ranged from good to poor. Data from each study was extracted through the use of meta-summary and critiqued. For improving the disease activity of IBD, an enriched oral supplement and wormwood were the only effective complementary treatments. The only effective treatment for maintaining remission in IBD was curcumin. Six out of the seven studies stated that their form of complementary or alternative therapy might have a beneficial effect on patients with IBD. Implications to Nursing Practice: Research suggests that more patients are turning to the use of CAM to try and treat their IBD. Therefore it is important for nurses and other health professionals to have access and knowledge of the benefits and adverse effects that CAM can have in certain diseases. Integrated healthcare systems could be a constructive way of managing patients use of CAM. Conclusion: The evidence from the studies shows that there is a great need for more randomised control trials to assess the safety and efficacy of more herbal and vitamin supplements for treatment of IBD.